Exploring teachers’ awareness and preparedness for cyberbullying in Malaysia: A systematic review (2018-2024) - Noorhafeza Herliani Adey; Kwan, Sharon Sam Mee; Carmella E. Ading (RSIS International, 2025)
This systematic review explores cyberbullying awareness and preparedness among Malaysian teachers, focusing on research from 2018 to 2024. Cyberbullying is a growing concern in Malaysia's primary schools, but teachers face challenges in effectively addressing it due to various factors. This review examines those challenges and the key factors that influence teachers' ability to handle cyberbullying. A systematic search was conducted using Scopus, Google Scholar, and My Cite databases, identifying 50 studies. After applying specific criteria, seven studies were selected, focusing on teachers’ perceptions, preparedness, and responses to cyberbullying in schools. A thematic analysis was performed to summarize the findings. The results showed that teachers’ awareness and preparedness varied significantly, with key factors such as professional training, socio-demographic characteristics, and institutional support influencing these differences. Teachers who had regular training and strong support from their schools felt more confident in dealing with cyberbullying. However, gaps in intervention strategies and psychological training were also identified. The review suggests that teacher training should include more focused programs, such as gamified learning and case-based workshops, to better prepare teachers. Future research should focus on long-term studies and culturally relevant training to help teachers address cyberbullying more effectively, creating safer learning environments for students.